2012
DOI: 10.1007/s00431-011-1644-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment trends in mucopolysaccharidosis I: findings from the MPS I Registry

Abstract: Our objective was to assess how the diagnosis and treatment of mucopolysaccharidosis I (MPS I) have changed over time. We used data from 891 patients in the MPS I Registry, an international observational database, to analyze ages at symptom onset, diagnosis, treatment initiation, and treatment allocation (hematopoietic stem cell transplantation, enzyme replacement therapy with laronidase, both, or neither) over time for all disease phenotypes (Hurler, Hurler–Scheie, and Scheie syndromes). The interval between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
0
18

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(121 citation statements)
references
References 33 publications
5
98
0
18
Order By: Relevance
“…Similar to ours, several studies from different countries showed that the diagnosis was established on average 2-3 years after the onset of symptoms (20,(25)(26)(27)(28)(29). In a case of MPS, since patients exhibit different organ/system manifestations, they present to physicians from different branches including pediatricians, geneticists, cardiologists, ophthalmologists, orthopedists, and neurosurgery, and are diagnosed with different disorders such as primary valvular heart disease, Perthes disease, congenital talipes equinovarus, spondyloepiphyseal dysplasia, cataract, rheumatoid arthritis, craniosynostosis, pseudoachondroplasia, and inguinal hernia (23,27,29,30).…”
Section: Discussionsupporting
confidence: 86%
“…Similar to ours, several studies from different countries showed that the diagnosis was established on average 2-3 years after the onset of symptoms (20,(25)(26)(27)(28)(29). In a case of MPS, since patients exhibit different organ/system manifestations, they present to physicians from different branches including pediatricians, geneticists, cardiologists, ophthalmologists, orthopedists, and neurosurgery, and are diagnosed with different disorders such as primary valvular heart disease, Perthes disease, congenital talipes equinovarus, spondyloepiphyseal dysplasia, cataract, rheumatoid arthritis, craniosynostosis, pseudoachondroplasia, and inguinal hernia (23,27,29,30).…”
Section: Discussionsupporting
confidence: 86%
“…Current therapies for MPS I include enzyme replacement therapy and bone marrow transplantation (Brooks 2002;Moore et al 2008;D'Aco et al 2012). While these therapies are effective for somatic tissue pathology, there are limitations with regard to the treatment of neuropathology.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Clinical manifestations Clinical manifestations of mucopolysaccharidosis type I (MPS I) show a chronic multisystemic and progressive course. [8] The disease is highly heterogeneous, spanning a spectrum of severity. Children with Hurler syndrome appear normal at birth and develop the characteristic appearance over the first years of life.…”
Section: Mucopolysaccharidosis Type Imentioning
confidence: 99%